An Industrial Quality Control Study on Universal Steel Smelting Co, Inc. - Bandayrel, Eugenio (College of Engineering, 2006)
Summary, Etc. The Industrial Quality Control study on the Universal Steel Smelting Co., Inc. aims to apply the knowledge brought about in the course of the study. The application of the basic concepts, principles, and the methods of Industrial Quality Control enhance the knowledge and develops the skill of the students in the given course. This study aims to do a statistical process control along with a process capability analysis on the given data by the Quality Management Department as well as with the data gathered by the group in the course of the study; specify control limits that will aid the company in further improving their production and doing their statistical methods that will further enhance their production of reinforced steel at high grade quality. The group?s study is restricted to three product sizes: 16 mm, 20 mm, and 25 mm. These are the bar sizes whose production processes are relatively stable and thus are more logical to use in the analysis. Through dialogues with the key personnel of the Quality Management Department and the Plant Production Manager, the group was able to identify the problems in the company that needs corrective action. After verifying these problems, the group found out that the company has been doing well with their processes but something can be done to further improve them. The main concern here is the process capability since it shows that the process is having a hard time in complying with the objectives or requirements of the company. Another would be that of using a control chart to properly guide the workers in finding assignable causes due mostly on data trends so as to properly do an out-of-control plan of action to remedy the process problem quickly. In addition to these, other problems that lead to the defects were identified such as machine malfunctions and unestablished parameter settings. Upon analysis of the problem, several recommendations were done to so as to improve the process of the company. Acquisition and the usage of a control chart will aid the workers in properly identifying assignable causes and remedy the problem quickly. Other major recommendations aside from the implementation of statistical process control include proper maintenance of machines; establishment of fixed parameter settings through the use of Design of Experiment; and conduction of chemical properties testing. Improvements through the use of Design of Experiment; and conduction of chemical properties and testing. Improvements through the increase in productivity and minimized variation in the products are the perceived effects of the implementation of the group's recommendations.